Stimulant Therapy Utilization for Neurocognitive Deficits in Mild Traumatic Brain Injury. (July 2022) - Coris, Eric E.; Moran, Byron; Sneed, Kevin; Del Rossi, Gianluca; Bindas, Bradford; Mehta, Shaan; Narducci, Dusty
Context: There are 3.8 million mild traumatic brain injuries (mTBIs) that occur each year in the United States. Many are left with prolonged life-altering neurocognitive deficits, including difficulties in attention, concentration, mental fatigue, and distractibility. With extensive data on the safety and efficacy of stimulant medications in treating attention deficit, concentration difficulties and distractibility seen with attention deficit disorder, it is not surprising that interest continues regarding the application of stimulant medications for the persistent neurocognitive deficits in some mTBIs. Evidence Acquisition: Studies were extracted from PubMed based on the topics of neurocognitive impairment, mTBI, stimulant use in mTBI, stimulants, and the association between attention deficit/hyperactivity disorder and mTBI. The search criteria included a date range of 1999 to 2020 in the English language. Study Design: Literature review. Level of Evidence: Level 4. Results: Currently, there is very limited literature, and no guidelines for evaluating the use of stimulant medication for the treatment of prolonged neurocognitive impairments due to mTBI. However, a limited number of studies have demonstrated efficacy and safety of stimulants in the treatment of neurocognitive sequelae of mTBI in the adult, pediatric, military, and athletic populations. Conclusion: There is limited evidence to suggest stimulant medication may be beneficial in patients with mTBI with persistent neurocognitive symtpoms. The decision to utilize stimulant medication for mTBI patients remains physician and patient preference dependent. Given the limited encouraging data currently available, physicians may consider stimulant medication in appropriate patients to facilitate the recovery of prolonged neurocognitive deficits, while remaining cognizant of potential adverse effects.